Canagliflozin, a Sodium Glucose Co-transporter 2 Inhibitor, for the Management of Type 2 Diabetes. Issue 3 (August 2014) - Brunton, Stephen; Reid, Timothy S.
Abstract : : The kidney plays a key role in glucose homeostasis and the pathophysiology of type 2 diabetes mellitus (T2DM). Sodium glucose co-transporter 2 (SGLT2) inhibitors are a new class of antihyperglycemic agents for the treatment of T2DM with a novel insulin-independent mechanism of action that targets the kidney. The SGLT2 inhibitors decrease renal glucose reabsorption, thereby increasing urinary glucose excretion and lowering plasma glucose levels in patients with hyperglycemia. SGLT2 inhibitor canagliflozin has demonstrated efficacy in improving glycemic control and reducing body weight and blood pressure as monotherapy or as add-on to other antihyperglycemic agents across a broad range of patients with T2DM. Canagliflozin is generally well tolerated, with increased incidences of specific adverse events that are related to the mechanism of SGLT2 inhibition. Findings suggest that canagliflozin is a useful treatment option for patients with T2DM.